The effects of changes in the sagittal plane alignment of running-specific transtibial prostheses on ground reaction forces - Tominaga, Shuichi; Sakuraba, Keisyoku; Usui, Fumio (Journal of Physical Therapy Science, 2015)
[Purpose] To verify the effects of sagittal plane alignment changes in running-specific transtibial prostheses on ground reaction forces (GRFs). [Subjects and Methods] Eight transtibial amputees who used running-specific prostheses during sprinting participated. The sprint movements were recorded using a Vicon-MX system and GRF measuring devices. The experiment levels were set as regularly recommended alignment (REG; the normal alignment for the subjects) and dorsiflexion or plantar flexion from the REG. [Results] The subjects were classified into fast (100-m personal best < 12.50 s) and slow (100-m personal best ≥ 12.50 s) groups. In both groups, there were no significant differences in the center of gravity speed; further, the difference in the stance time was significant in the slow group but not in the fast group. Significant differences were observed in the step length for the fast group, whereas the stance time and step rate significantly differed in the slow group. The GRF impulse showed significant differences in the vertical and braking directions in both groups. [Conclusion] The GRFs are affected by sagittal plane alignment changes in running-specific prostheses. Moreover, our results suggest that the change in GRFs along with the altered sagittal plane alignment influenced the step length and step rate.